ANALISIS KEBUTUHAN PEMAHAMAN BUDAYA DIGITAL PADA GENERASI X DAN BABY BOOMERS - Gendro Salim; Ahsanun Naseh Khudori; M. Syauqi Harris (Yayasan Nusantara Hasana Berdikari, 2025)
During 2 (two) decades of assisting entrepreneurs in running their businesses, researchers have interacted with hundreds of entrepreneurs, most of whom are Baby Boomers born between 1946-1964 and Generation X born between 1965-1980, requiring a customized approach because these two generations have characteristics, preferences. Where it is precisely this generation that is very behind with digitalization and technology. Their desire for transformation is not supported by their ability to absorb information so quickly, with unfamiliar jargon. Coupled with the ability of digital actors, who also cannot explain analogies that can be accepted by this generation. In the context of writing this journal, the researcher tried an empathetic approach, collecting data with questionnaires from the clients of the researcher, so as to illustrate the unrest. What priorities must be done, in order to break this deadlock, so as to provide a wider perspective to the community, in order to improve the capabilities of both parties, both service providers and recipients of digital services. In this journal, the researcher specializes in Understanding Digital Culture in Baby Boomers and Generation X.